2006
DOI: 10.1142/s0219877006000752
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies of Advanced Manufacturing Technology Implementation in Small Companies

Abstract: Issues of Advanced Manufacturing Technology (AMT) implementation have been extensively covered in the literature in regard to large companies; however, exclusive examination of the impact of AMT on small companies remains under researched. This examination of ten case study companies demonstrates the potential benefits of AMT use, as each of the companies achieved positive outcomes from AMT. However, the benefits achieved did not always meet the companies' expectations. Analysis of the experiences of the compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…It was also shown that developing integrated benefits in AMT adoption is more difficult than the development of a technology's inherent capabilities. These finding concur with the results of previous research into small company AMT implementation [16].…”
Section: Managerial Impactsupporting
confidence: 93%
See 1 more Smart Citation
“…It was also shown that developing integrated benefits in AMT adoption is more difficult than the development of a technology's inherent capabilities. These finding concur with the results of previous research into small company AMT implementation [16].…”
Section: Managerial Impactsupporting
confidence: 93%
“…Table 1 presents an overview of companies interviewed in the retrospective stage and the AMT discussed. The results of the retrospective stage indicated three important issues for the implementation of AMT in small companies: consideration of the inherent and integrated benefits of the proposed AMT; consideration of company technological experience; and, availability of vendor or other support mechanisms [16]. Inherent benefits refer to a match between company requirements and the capabilities of an installed technology.…”
Section: Retrospective Case Studiesmentioning
confidence: 99%
“…The object of the research is defined according to Walters et al (2006): advanced manufacturing technology is "a group of integrated hardware-based and software-based technologies, which if properly implemented, monitored and evaluated, lead to improving the efficiency and effectiveness of the firm in manufacturing a product or providing a service".…”
Section: Literature Review On Amt: Concept Benefits and Criteria Of mentioning
confidence: 99%
“…The studies of Simolow (2005) on CAD/CAM application, status and impact in Nigerian industrial sector have given an very good overview of the CAD/CAM applications in various industrial sectors and findings were useful in justifying the implementation of CAD/CAM. The impact of Advanced Manufacturing technology on welsh companies ,a study carried out by Walters (2006) has also given a comprehensive case studies on 7 companies which gives evidence in application of AMT on those industries. This chapter also considered the various technologies and literature on those technologies to support the argument.…”
Section: Discussionmentioning
confidence: 99%
“…In their article Miliward et al . (2006) disclose that many companies in US are failing to achieve their anticipated benefits following implementation, mainly due to the fact that many of the benefits associated with advance manufacturing technologies (CAD/CAM) are intangible.…”
Section: Benefits Of Cad/cammentioning
confidence: 99%